On the energy of closed shadow graphs - Morisca, Melody Mae L. (Animo Repository, 2024)
The energy and d-energy of a graph is the sum of the absolute value of eigenvalues of the graph’s adjacency matrix and distance matrix respectively. In 2017, S. Vaidya and K. Popat determined the energy of a shadow graph of a connected graph. In this study, we determine the eigenvalues and d-eigenvalues of a closed shadow graph and closed m-shadow graph. Using those spectrum and distance spectrum that we obtained, we computed the energy and distance energy of closed shadow graph and closed m-shadow graph. We also introduce a new graph operation called anti-shadow of a graph and determine the spectrum of the graph obtained from the graph operator.